Effect of Plasminogen Activator Inhibitor-1 on Tissue-Type Plasminogen Activator-Induced Fibrinolysis - Carr, Marcus E, Jr.; Krishnamurti, C; Alving, B M (Thrombosis and Haemostasis, 1992)
The effect of fibrin on the interaction of human recombinant single-chain tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) was studied in normal rabbit plasma and in plasma with high levels of native PAI-1. t-PA was added to diluted plasma containing calcium (10 mM) and 125I-fibrinogen at 37° C. Clotting was initiated with human thrombin, and lysis was monitored both turbidimetrically and by release of 125I-fibrin degradation products (fdp). The activity of t-PA (50 IU/ml) was rapidly reduced to 15% of the initial value in plasma containing PAI-1 (23 AU/ml). When thrombin and t-PA were added simultaneously to the plasma, more than 70% of the activity was retained through incorporation of t-PA into the fibrin clot. t-PA-induced fibrinolysis in PAI-1 enriched plasma was further delayed when the temperature was reduced from 37 to 25° C. Turbidimet-ric and 125I-fdp release data provided complementary information. The former technique traced fiber dissolution, while the latter reflected network integrity. These results indicate that t-PA-induced fibrinolysis in PAI-1 enriched plasma is modulated by the presence of fibrin and by temperature.